1983
DOI: 10.1007/bf01658085
|View full text |Cite
|
Sign up to set email alerts
|

Surgical aspects of thyroid autonomy in multinodular goiter

Abstract: In a prospective study of 217 consecutive patients with multinodular goiter selected for surgical treatment, 43% had significant autonomous thyroid hormone secretion as evidenced by TRH unresponsiveness [TSH<1.0 ΜU/ml after intravenous (200 Μg) or oral (40 mg) TRH], with normal values of the FT4‐Index and FT3‐Index (preclinical hyperthyroidism) in 74%, and with hyperthyroidism in 26% of these cases. The amount of autonomous thyroid hormone secretion increased with the mean goiter weight and age of patients. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…This coincides with an increased incidence of multinodular goitre during this period of life. Previous studies (Evered et al 1974;Gemsenjäger et al 1976) have shown that even in the absence of iodine deficiency this type of goitre is very frequently unresponsive to T3 and to TRH. This unresponsiveness is more often seen in elderly patients (Emrich & Bahre 1978;Smeuler et al 1977).…”
Section: Discussionmentioning
confidence: 97%
“…This coincides with an increased incidence of multinodular goitre during this period of life. Previous studies (Evered et al 1974;Gemsenjäger et al 1976) have shown that even in the absence of iodine deficiency this type of goitre is very frequently unresponsive to T3 and to TRH. This unresponsiveness is more often seen in elderly patients (Emrich & Bahre 1978;Smeuler et al 1977).…”
Section: Discussionmentioning
confidence: 97%
“…Only Waldstron et al 15 made references to a surgical indication rate of 50% in patients with recurrence. Gemsenjager et al 20 and Barbier et al 21 agreed that the best way to avoid a recurrence is to remove all pathological tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The transient rise discovered may simply be ex¬ plained by the fact that the high normal pre¬ operative level of serum TT3 normalized after operation. It is well established that nodular goitres are able to develop varying degrees of functional autonomy resulting in preclinical hyperthyroidism with raised serum TT3 (Gemsenjäger et al 1976;Blichert-Toft et al 1978). Actually, some of our patients probably had borderline T3-thyrotoxicosis.…”
Section: Discussionmentioning
confidence: 61%
“…Recent studies, however, have questioned the rational basis for routine in¬ take of thyroid hormone after simple goitre resec¬ tion in non-endemic areas (Blichert-Toft et al 1978, 1979Matte et al 1981;Geerdsen & Hee 1982;Persson et al 1982). In these studies, im¬ paired thyroid function after resection was a rare finding, and thyroid replacement therapy does not seem to be efficacious in preventing regrowth of goitre (Persson et al 1982;Gemsenjäger et al 1983). …”
mentioning
confidence: 94%